Role of Long Noncoding RNAs and Circular RNAs in Nerve Regeneration - Yao, Chun; Yu, Bin (Frontiers in Molecular Neuroscience, 2019)
Nerve injuries may cause severe disability and affect the quality of life. It is of great importance to get a full understanding of the biological processes and molecular mechanisms underlying nerve injuries to find and target specific molecules for nerve regeneration. Numerous studies have shown that noncoding RNAs (ncRNAs) participate in diverse biological processes and diseases. Long noncoding RNAs (lncRNAs) and circular RNAs (circRNAs) are two major groups of ncRNAs, which attract growing attention. The altered expression patterns of lncRNAs and circRNAs following nerve injury suggest that these ncRNAs might be associated with nerve regeneration. This review will give a brief introduction of lncRNAs and circRNAs. We then summarize the current studies on lncRNAs and circRNAs following peripheral nerve injury and spinal cord injury (SCI). Typical lncRNAs and circRNAs are introduced to illustrate the diverse molecular mechanisms for nerve regeneration. In addition, we also discuss some issues to be addressed in future investigations on lncRNAs and circRNAs.